Nerds on Wall Street : math, machines, and wired markets - Leinweber, David, 1952- (Wiley, 2009)
An intriguing look at how technology is changing financial markets, from an innovator on the frontlines of this revolution. Nerds on Wall Street tells the tale of the ongoing technological transformation of the world's financial markets. The impact of technology on investing is profound, and author David Leinweber provides readers with an overview of where we were just a few short years ago, and where we are going. Being a successful investor today and tomorrow--individual or institutional--involves more than stock picking, asset allocation, or market timing: it involves technology. And Leinwe.